Research on the Synergistic Mechanism of Internal Control and Risk Management in Enterprises (Journal of Global Humanities and Social Sciences, 2026)
The risks enterprises face today are complex and diverse, primarily stemming from intensified market competition driven by economic globalization. Therefore, to achieve steady and forward-moving development, research on the synergistic mechanism between internal control and risk management within enterprises is urgently needed. Internal control serves as the foundation for risk management, while risk management provides solutions for enterprises to mitigate risks. This study analyzes the internal connections between their coordinated development, elucidates the significance of internal control for enterprise growth, categorizes current risk management approaches, and clarifies their aligned objectives and collaborative relationship. However, numerous obstacles to implementation persist in practice. Targeted optimization pathways are proposed to provide theoretical foundations for future enterprise development.